Development of Novel Approaches for the Treatment of Cutaneous Candidiasis - Singh, Abhay Kumar; Mazumder, Rupa; Dogra, Anmol (Current Pharmaceutical Design, 2025)
The main culprit behind cutaneous candidiasis, a fungal infection that can lead to major dermatological and systemic health problems, is <span class=
Keywords: burning